Staying Roman : conquest and identity in Africa and the Mediterranean, 439-700 - Conant, Jonathan, 1974- (Cambridge studies in medieval life and though ; fourth series ;, 2012)
"In 416, when preaching a sermon on the psalms in late Roman Carthage, Augustine was able to ask his audience, 'Who now knows which nations in the Roman empire were what, when all have become Romans, and all are called Romans?'1 Yet already by the time Augustine addressed his Carthaginian audience the continued unity of the Roman Mediterranean was being called into question. The defeat and death of the Roman emperor Valens at Adrianople in 378 had set the stage for a new phase of conflict between the empire and its non-Roman neighbours ; and over the course of the fifth century Roman power collapsed in the West, where it was succeeded by a number of sub-Roman kingdoms. Questions that had seemed trivial to Augustine were suddenly and painfully alive : what did it mean to be 'Roman' in the changed circumstances of the fifth and later centuries? And (from a twenty-first-century perspective) what became of the idea of Romanness in the West once Roman power collapsed?"--